Recession and Resilience: Labor Market Consequences of Starting College in a Bad Economy - Eleanor J. Choi; Daeyoung Jeong; Chae Lee; Kyuseob Yu (Institute of Labor Economics (IZA), 2025)
This study examines the impact of economic conditions at college entry on post-graduation labor market outcomes, focusing on behavioral responses related to job market preparation and career advancement. Exploiting variation in regional unemployment rates within college entry cohorts, we utilize the large and unexpected recession triggered by the Asian Financial Crisis in South Korea as a natural experiment. Using data from the Korean Labor and Income Panel Study, we find that individuals who begin their undergraduate studies under more adverse economic conditions exhibit higher employment probabilities and earnings during the first decade after graduation. Further analysis of activities during college and early career stages indicates that the improved labor market outcomes are driven by greater effort devoted to education, training, and job search aimed at enhancing employment prospects. To explain these behavioral responses, we develop a theoretical framework based on the concept of ambiguity aversion.
Keywords: E32; J24; I23; D81; 330; economic crisis; college entrants; labor market outcomes; ambiguity aversion